2011
DOI: 10.1071/he11240
|View full text |Cite
|
Sign up to set email alerts
|

Letter – Lessons learnt from a pilot bicycle program with community mental health service consumers

Abstract: Physical activity improves mental health. Building on previous work promoting cycling in the general community, we trialled an innovative cycling program for mental health service consumers in the former Sydney South West Area Health Service. The poor physical health of people with a mental illness is well documented. Increasing consumer's physical health is difficult and the literature surrounding the issue is limited. One study found that outside activity significantly improves self esteem and mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the scientific literature, several studies have analyzed the effects of the bicycle training courses in the urban context for adults settled in Australia [ 26 , 27 ] and the United Kingdom [ 28 ]. Among the Australian studies, Telfer et al [ 26 ] observed an increase in the frequency of trips by bicycle and an improvement in basic skills and confidence to ride the bicycle after the participation of adults in the cycling program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the scientific literature, several studies have analyzed the effects of the bicycle training courses in the urban context for adults settled in Australia [ 26 , 27 ] and the United Kingdom [ 28 ]. Among the Australian studies, Telfer et al [ 26 ] observed an increase in the frequency of trips by bicycle and an improvement in basic skills and confidence to ride the bicycle after the participation of adults in the cycling program.…”
Section: Introductionmentioning
confidence: 99%
“…Among the Australian studies, Telfer et al [ 26 ] observed an increase in the frequency of trips by bicycle and an improvement in basic skills and confidence to ride the bicycle after the participation of adults in the cycling program. Devine et al [ 27 ] reported an improvement in social relationships and an increase of cycling trips. Moreover, in terms of changes in cycling levels, similar results were found in the United Kingdom, where Johnson et al [ 28 ] reported higher cycling frequency after the training than beforehand.…”
Section: Introductionmentioning
confidence: 99%